Role of the "Ana Goitia" diabetes day hospital in the reduction of maternal and infant morbimortality - Ramos, Cecilia Noelia; Acosta, Estela Mercedes (SCT Proceedings in Interdisciplinary Insights and Innovations, 2024)
Background: Gestational diabetes is any degree of carbohydrate metabolism disorder that begins or is first diagnosed during pregnancy. It is the most common metabolic disease of pregnancy and a public health problem due to the high prevalence and maternal-fetal complications it can cause. For this reason, it is of vital importance the medical management in the detection of risk factors for the prevention of gestational diabetes, early diagnosis and adequate treatment and follow-up to reduce morbidity and mortality. Material and methods: A systematic literature review and a descriptive study of medical records of patients attended during the period 2022 in the diabetes day hospital of a mother and child hospital in the province of Buenos Aires were carried out. Results: It was observed that, out of 112 births to diabetic mothers, 100% of the women had a normal puerperium, 81% of the babies were born weighing less than 4000g and 9% had fetal macrosomia. Conclusion: In conclusion, the role of the day hospital has proven to be of great importance in reducing complications and promoting a healthy pregnancy. Interdisciplinary collaboration and personalized care are key to address maternal and infant morbidity and mortality